2021
DOI: 10.1130/g48940.1
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake doublet revealed by multiple pulses in lacustrine seismo-turbidites

Abstract: Earthquake doublets have been described in fault systems around the world but have not yet been confidently resolved in paleoseismic records. Our current knowledge is limited to historical occurrences, preventing researchers from uncovering potential patterns or recognizing common fault behavior. Identification of prehistoric doublets is thus of crucial importance for adequate seismic hazard assessment and risk mitigation. We developed a new methodology to reveal the sedimentary imprint of earthquake doublets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…six events with magnitudes ranging from MW 5.1-6.4 within five months in the Friuli region in 1976 (Carulli and Slejko, 2005) and two events of MW 5.5 to 5.7 (± 0.4) in central Tyrol in 1670 and 1689 (Stucchi et al, 2013). The time periods between these historical earthquake successions are far below the age uncertainty of radiocarbon-based age-depth models and would remain undifferentiated unless multiple consecutive earthquake imprints can be distinguished within the sedimentary record (Wils et al, 2021). Therefore, it cannot be excluded that one or the other of the presented paleoearthquake scenarios actually represent two or more closely spaced and consecutive earthquakes with slightly smaller magnitudes.…”
Section: Discussion Of the Individual Paleo-earthquake Scenariosmentioning
confidence: 94%
“…six events with magnitudes ranging from MW 5.1-6.4 within five months in the Friuli region in 1976 (Carulli and Slejko, 2005) and two events of MW 5.5 to 5.7 (± 0.4) in central Tyrol in 1670 and 1689 (Stucchi et al, 2013). The time periods between these historical earthquake successions are far below the age uncertainty of radiocarbon-based age-depth models and would remain undifferentiated unless multiple consecutive earthquake imprints can be distinguished within the sedimentary record (Wils et al, 2021). Therefore, it cannot be excluded that one or the other of the presented paleoearthquake scenarios actually represent two or more closely spaced and consecutive earthquakes with slightly smaller magnitudes.…”
Section: Discussion Of the Individual Paleo-earthquake Scenariosmentioning
confidence: 94%
“…Perspectives for the future evolution of the field include the development of new high-resolution methods such as CT scanning, providing sedimentological fabric characterization [209], hyperspectral imaging providing automatic determination of event deposits at very high resolution [203,204] (see also Jacq et al, in this issue), and clustering and end-member modeling techniques based on grain-size or XRF core scanner data [302]. Investigating multiple lake systems in the same area is also encouraged to better estimate the spatial imprint of specific events (e.g., earthquake, flood, tsunami, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…As these sedimentary structures are a clear indication of deposition during a flow process, they can, for example, be used to distinguish a fallout tephra deposit (massive) from volcanic material deposited or reworked by a turbidity current (cross or parallel laminations) (Figure 13B). Further, 3D-microfacies analysis of such basal turbidite sands has also permitted the determination of the grain orientation and thereby the paleoflow direction of separate sand layers within a single (amalgamated) earthquake-induced turbidite [209] or for tsunami [210] and hurricane [211] deposits. Microfacies analysis of event deposits using thin sections and µCT scans has further enabled researchers to visualize bioturbation at the top and base of turbidites (Figure 13A; Figure 11A; [18,208]), to identify small-scale grading in turbidites [15,208], to identify internal mud clasts [126], to assess the state of fragile diatom frustules [15], and to detect (crypto)tephras (Figure 13A; [15,18,212]).…”
Section: Sedimentary Structures and Microfaciesmentioning
confidence: 99%
“…Alternatively, amalgamated turbidites originating from different slopes may also show different flow directions (e.g. Wils et al, 2021), but clear coarsening between separate pulses was not observed here (Van Daele et al, 2017) so this interpretation is not favoured. (3) Faint turbidite layering, related to progressive grain-size distribution changes, fitting the description of amalgamated turbidites (Van Daele et al, 2017).…”
Section: Inferred Depositional Mechanisms Corinth Rift Event Depositsmentioning
confidence: 95%